Pengembangan Aplikasi Android Integrated Ebooks untuk Pembelajaran Tematik di Sekolah Dasar - Alvin Wardanartama; Muh. Arafik; Arda Purnama Putra; Alvin Wardanartama; Muh. Arafik (Universitas Negeri Malang, 2023)
Abstract: Media is one of the needs of the Indonesian people today. Education in Indonesia cannot be separated from technological media such as laptops and smartphones. The purpose of this research is to produce an effective and efficient learning product or media for school children, especially in elementary schools. This research was conducted using the Dick and Carey research method. Valid according to media experts (Mustika Mentari, S.Kom, M.Kom), material experts (Dr. Siti Mas'ula, M.Pd), users/teachers (Sunarsih, S.Pd and Bambang Yogianto, S.Pd), as well as attractive to students of SDN 3 Pringgodani and SDN 1 Sumberbening. This research method uses R&D development according to Dick & Carey including: 1) analysis of needs and general goals, 2) analysis of learning, 3) analysis of teachers, students, and infrastructure, 4) selecting and determining content according to needs, 5) developing application designs, 6) developing the initial product, 7) designing and conducting formative evaluation, 8) revising the product, 9) making the final product. The instruments used were field observations, validation instruments, and student questionnaires. The results of media validation were 90 percent (very valid), material validation 86 percent (very valid), user/teacher validation 86 percent (valid), and trials with students 85 percent (very valid) and 87 percent (very valid). The results of the validity presentation obtained by the researcher were 86.8 percent (very valid). Therefore, it can be concluded that this product can be said to be appropriate for using media in the learning process in grade III elementary schools. Abstrak: Media merupakan salah satu kebutuhan masyarakat Indonesia pada jaman sekarang. Pendidikan Indonesia tidak mungkin lepas dari media elektronik seperti laptop dan smartphone. Tujuan peneliti mengambil pengembangan ini yaitu supaya dihasilkannya media aplikasi pembelajaran yang efektif dan efisien untuk anak sekolah terutama di sekolah dasar. Peneliti menggunakan metode Dick & Carey. Valid menurut ahli media (Mustika Mentari, S.Kom, M.Kom), ahli materi (Dr. Siti Mas’ula, M.Pd), pengguna/guru (Sunarsih, S.Pd dan Bambang Yogianto, S.Pd), serta menarik bagi siswa SDN 3 Pringgodani dan SDN 1 Sumberbening. Metode penelitian ini menggunakan pengembangan R&D menurut Dick dan Carey meliputi : 1) analisis kebutuhan dan tujuan umum, 2) analisis pembelajaran, 3) analisis guru, siswa, dan sarpras, 4) memilih dan menentukan konten sesuai kebutuhan, 5) mengembangkan rancangan aplikasi, 6) mengembangkan produk awal, 7) merancang dan melakukan evaluasi formatif, 8) melakukan revisi produk, 9) membuat produk akhir. Instrumen yang digunakan yaitu observasi lapangan, instrumen validasi, dan respon angket siswa. Hasil validasi media 90 persen (sangat valid), dari validasi materi 86 persen (sangat valid), dari validasi pengguna/guru 86 persen (valid), dan dari uji coba dengan siswa 85 persen (sangat valid) dan 87 persen (sangat valid). Hasil presentasi kevalidan yang diperoleh peneliti yaitu sebesar 86,8 persen (sangat valid). Peneliti menyimpulkan bahwa produk ini dapat dikatakan layak digunkan media dalam proses belajar di kelas III Sekolah Dasar.